The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/00223980.2018.1449729
|View full text |Cite
|
Sign up to set email alerts
|

The Conceptualization of Team Flow

Abstract: Despite the noted potential for team flow to enhance a team's effectiveness, productivity, performance, and capabilities, studies on the construct in the workplace context are scarce. Most research on flow at the group level has been focused on performance in athletics or the arts, and looks at the collective experience. But, the context of work has different parameters, which necessitate a look at individual and team level experiences. In this review, we extend current theories and essay a testable, multileve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 114 publications
3
69
0
Order By: Relevance
“…A concept with a high potential for fostering team effectiveness is the concept of team flow ( van den Hout et al, 2018 ). Team flow is a shared experience of flow, characterized by the pleasant feeling of absorption in an optimally challenging activity ( Peifer and Engeser, 2021 ), and of optimal team-interaction during an interdependent task ( van den Hout et al, 2018 ). Research on team flow is still scarce and particularly lacking for virtual teams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A concept with a high potential for fostering team effectiveness is the concept of team flow ( van den Hout et al, 2018 ). Team flow is a shared experience of flow, characterized by the pleasant feeling of absorption in an optimally challenging activity ( Peifer and Engeser, 2021 ), and of optimal team-interaction during an interdependent task ( van den Hout et al, 2018 ). Research on team flow is still scarce and particularly lacking for virtual teams.…”
Section: Introductionmentioning
confidence: 99%
“…A concept with a high potential for fostering trust and team effectiveness is the concept of team flow ( van den Hout et al, 2018 ). Previous research already indicated that the concept of flow can be a meaningful antecedent of trust in virtual settings ( Bilgihan et al, 2015 ), whereby the presence of flow increased the perception of trust.…”
Section: Introductionmentioning
confidence: 99%
“…In the management science and organizational behavior literatures, teams are defined as: two or more individuals who perform organizationally relevant tasks, share at least one common goal, interact socially, have task interdependence, maintain and manage boundaries and roles, and are embedded in a larger organizational context that sets objectives, boundaries, constraints on the team, and influences exchanges with other teams (Kozlowski and Bell, 2003). Teams include features such as collective ambition, common goals, alignment of individual goals, high skill differentiation, open communication, safety, and mutual commitment (van der Hout et al, 2018). While teams operate as distinguishable (and measureable) work units partially independent of (but subsumed within) the organization, the organization constrains and sets the overall objectives of the team (Kozlowski and Bell, 2003).…”
Section: What Can We Learn From Human Teams?mentioning
confidence: 99%
“…Second, how can researchers enable team-level flow, peak performance, and positive psychological experiences such as cohesion within HATs? Team flow is an emergent topic within team sciences and requires volitional attention and action toward team goals/activities (van der Hout et al, 2018). How can we establish and maintain unit cohesion with the introduction of machines as teammates?…”
Section: Research Gapsmentioning
confidence: 99%
“…as well as generating a sense of unity(Van den Hout et al, 2018) are vital. Correspondingly, LSP workshops place an emphasis on equal participation in order to include each member's perspective, knowledge and experience.…”
mentioning
confidence: 99%